Adiabatic Quantum Computation With Flux Qubits, First Experimental Results; IEEE Transactions On Applied Superconductivity; Vol. 17, iss. 2 - Ploeg S. H. W. van der; Izmalkov A.; Grajcar M.; Hubner U.; Linzen S.; Uchaykin S. V. Sergey Victorovich; Wagner Th.; Smirnov A. Yu.; Brink A. M. van den; Amin M. H. S.; Zagoskin A. M.; Il’ichev E.; et al. (2007, 2007)
Title screen